Closed-loop vagus nerve stimulation aids recovery from spinal cord injury - Michael P. Kilgard; Joseph D. Epperson; Emmanuel A. Adehunoluwa; Chad Swank; Amy L. Porter; David T. Pruitt; Holle L. Gallaway; Christi Stevens; Jaime Gillespie; Dannae Arnold; Mark B. Powers; Rita G. Hamilton; et al. (Nature, 2025)
Abstract Decades of research have demonstrated that recovery from serious neurological injury will require synergistic therapeutic approaches. Rewiring spared neural circuits after injury is a long-standing goal of neurorehabilitation1,2. We hypothesized that combining intensive, progressive, task-focused training with real-time closed-loop vagus nerve stimulation (CLV) to enhance synaptic plasticity3 could increase strength, expand range of motion and improve hand function in people with chronic, incomplete cervical spinal cord injury. Here we report the results from a prospective, double-blinded, sham-controlled, randomized study combining gamified physical therapy using force and motion sensors to deliver sham or active CLV (ClinicalTrials.gov identifier NCT04288245). After 12 weeks of therapy composed of a miniaturized implant selectively activating the vagus nerve on successful movements, 19 people exhibited a significant beneficial effect on arm and hand strength and the ability to perform activities of daily living. CLV represents a promising therapeutic avenue for people with chronic, incomplete cervical spinal cord injury.